GENRE CHARACTERISTICS OF DETECTIVE WORKS (American Journal of Interdisciplinary Research and Development, 2024)
The article analyzes the genre characteristics and types of detective works. It explores the distinctive features of detective literature, its structure and main elements, as well as the differences between the subgenres within the genre. The article focuses on scientific approaches to determining the genre of detective works, communicative and structural analysis methods, genre categories, stylistic features, and specific characteristics of detective stories. It also examines various forms of detective works and their process of transformation.